2017
DOI: 10.1021/acs.chemmater.6b05458
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Superconductivity in RbLn2Fe4As4O2(Ln = Sm, Tb, Dy, and Ho)

Abstract: We have synthesized four iron-based oxyarsenide superconductors RbLn 2 Fe 4 As 4 O 2 (Ln = Sm, Tb, Dy and Ho) resulting from the intergrowth of RbFe 2 As 2 and LnFeAsO.It is found that the lattice match between RbFe 2 As 2 and LnFeAsO is crucial for the phase formation. The structural intergrowth leads to double asymmetric Fe 2 As 2 layers that are separated by insulating Ln 2 O 2 slabs. Consequently, the materials are intrinsically doped at a level of 0.25 holes/Fe-atom and, bulk superconductivity emerges at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 36 publications
6
34
1
Order By: Relevance
“…We found that T c decreases (increases) with the intra-bilayer (inter-bilayer) spacing. 12,14 In the present K-and Cs-containing series, similar behaviour is expected (here we cannot give the structural correlation plot because some samples' purity is not good enough for a reliable structural refinement).…”
Section: Lnsupporting
confidence: 75%
See 2 more Smart Citations
“…We found that T c decreases (increases) with the intra-bilayer (inter-bilayer) spacing. 12,14 In the present K-and Cs-containing series, similar behaviour is expected (here we cannot give the structural correlation plot because some samples' purity is not good enough for a reliable structural refinement).…”
Section: Lnsupporting
confidence: 75%
“…Then we also succeeded in synthesizing the first 12442-type oxyarsenide, RbGd 2 Fe 4 As 4 O 2 , whose T c achieves 35 K. 13 With the substitution of rare-earth elements, four additional oxyarsenides in the Rb-containing series have been found. 14 These studies show that the lattice match between 122 and 1111 blocks is important, as suggested in our earlier proposal. 2 For this reason, the lattice-match paradigm can be employed for the exploration of the remaining 12442-type members.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Note that the deviations are the opposite in hole-doped 12442-type FeSCs, the latter of which show larger hAs and smaller  values (e.g., hAs1 = 1.405 Å, hAs2 = 1.436 Å; 1 =108.0  , 2 =106.8  for KCa2Fe4As4F2 16 ). Unlike the (T) behavior in hole-doped 12442-type FeSCs, [16][17][18][19][20] here neither a convex curvature at around 150 K nor a linear temperature dependence below 100 K is seen. The low-temperature (40 K < T < 100 K) normal-state resistivity actually satisfies a power relation,  = 0 + AT n .…”
mentioning
confidence: 72%
“…In all four of these examples, the species above and below an Fe-As sheet are the same, preserving the glide-symmetry across the Fe plane. [26,27], AR 2 Fe 4 As 4 O 2 (Ae = Ca, Sr, Ba, Eu; A = K, Rb, Cs; R = lanthanide) [28,29,30] ]. In these families, two different alternating layers separate the Fe-As sheets.…”
Section: Structuresmentioning
confidence: 99%